RESTRICTIONS BROUGHT TO THE RIGHT TO PENSION – AS A COMPONENT OF THE RIGHT OF LIVING STANDARD - Oana ŞARAMET (The International Conference European Unions History, Culture and Citizenship, University of Piteşti,. Faculty of Law and Administrative Studies, 17-18 April 2009, 2009)
The Universal Declaration of Human Rights proclaimed by the General Assembly of United Nations at 10th of December 1948, didn’t settle, expresis verbis, among the fundamental rights and freedoms of human rights, a special rights that, no matter what its name is, may oblige the international community to respect a certain living standard for the human beings, be it decent or sufficient. Still, if we read carefully the provisions of Art.25, paragraph 1 from the Universal Declaration of Human Rights we can identify some specific aspects regarding this special right. After adopting the international document, some states, among which we must mention Romania, appreciated the opportunity of settling the constitutional consecration of this right, even if it wasn’t expressly settled but rather incorporated among the provisions of another right.
Keywords: living standard; fundamental right; The Universal Declaration of Human Rights